Análise comparativa de nbrs de terminologias e o Dicionário Houaiss - Cruz, Cleide Lemes da Silva (2012)
This paper presents a comparative analysis between two Brazilian Regulatory Standards (NBRs), namely NBR 6502:1995 - Rocks and Soils and NBR 10703:1989 - Soil degradation and Houaiss Dictionary (2009) in order to classify as NBRs technical glossaries, according to the methodology of evaluation of dictionaries postulated by Faulstich (1998). The analysis covers also a brief overview focusing on the macrostructure and microstructure of the dictionary Houaiss; followed completing the screenplay for evaluation of scientific dictionaries and glossaries, and finally, the comparison of the macrostructure and microstructure of the dictionary Houaiss and NBRs.